Consequences of warfarin suspension after major bleeding in very elderly patients with non valvular atrial fibrillation - Zoppellaro, Giacomo; Granziera, Serena; Bertozzo, Giulia; Denas, Gentian; Marigo, Lucia; Petruzzellis, Florinda; Jose, Seena Padayattil; Rossi, Katia; Nante, Giovanni; Pengo, Vittorio (Thrombosis and Haemostasis, 2017)
Supplementary Material to this article is available online at www.thrombosis-online.com.